Where Does the Pregnant Women Searching for Their Information Need? - Marlina, Ekawati; Kusumaningrum, Dwiatri; Yudhanto, Seno (UI Scholars Hub, 2018)
Pregnant women tend to be more concern with the health and food issue. During pregnancy, women will have physiological changes, such as intestinal disorders, metabolic diseases, and obesity. They tend to reduce consume of food with pregnancy-related health risk. In order to achieve a healthy pregnancy, information related to health and food issue are needed. Pregnant women were actively seek information from a variety of sources. The research method used is literature review, we would like to identify which source of information that most used by pregnant to meet their information need and how is their belief about the sources. The conclusion of this study that information required by pregnant women related with information regarding medicine or medication use in pregnancy, nutrition, and health disorders. Dominant information used by pregnant women were health practitioners, online information, and family/friends. Although used by many pregnant women, the internet believed as an unreliable source of health information. Health practitioners were the main trusted information sources. This study is essential for information provider in designing healthy living information and educating health literacy for pregnant women.